Noninvasive Mechanical Ventilation Guidelines and Standard Protocols for Noninvasive Mechanical Ventilation in Patients with High-Risk Infections - Keymel, Stefanie (Noninvasive Ventilation in High-Risk Infections and Mass Casualty Events, 2013)
Noninvasive ventilation (NIV) is associated with lower rates of endotracheal intubation and decreased mortality in patients with acute respiratory failure. Therefore, NIV should be preferred to invasive ventilation whenever possible [1]. In clinical settings, most of the patients were treated by NIV because of pulmonary edema or exacerbated chronic obstructive lung disease (COPD) [2]. With endemic and high-risk infection, most of the critically ill patients develop acute lung injury (ALI) and/or acute respiratory distress syndrome (ARDS). Furthermore, NIV, an “aerosol-producing factor” might be regarded as a high-risk procedure for medical staff [3].